2001
DOI: 10.1200/jco.2001.19.17.3771
|View full text |Cite
|
Sign up to set email alerts
|

Purging of Autologous Peripheral-Blood Stem Cells Using CD34 Selection Does Not Improve Overall or Progression-Free Survival After High-Dose Chemotherapy for Multiple Myeloma: Results of a Multicenter Randomized Controlled Trial

Abstract: This phase III trial demonstrates that although CD34 selection significantly reduces myeloma cell contamination in PBPC collections, no improvement in disease-free or overall survival was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
2
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(121 citation statements)
references
References 28 publications
2
116
2
1
Order By: Relevance
“…There were no deaths or significant bleeding episodes; 14 patients (44%) required hospitalization for neutropenic fever. Median days of grade 3 or 4 neutropenia or thrombocytopenia were 7 (2-20) and 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Median mobilization days, CD34 þ cells/kg and total leukaphereses were 16 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 12.1 million (2.6-52.8), and 2 (1)(2)(3)(4)(5) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…There were no deaths or significant bleeding episodes; 14 patients (44%) required hospitalization for neutropenic fever. Median days of grade 3 or 4 neutropenia or thrombocytopenia were 7 (2-20) and 8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Median mobilization days, CD34 þ cells/kg and total leukaphereses were 16 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), 12.1 million (2.6-52.8), and 2 (1)(2)(3)(4)(5) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…15 Although CD34 þ cell selection has been used as a purging modality in the clinic, this has been shown in randomized trials not to benefit patients from PFS or overall survival. 7 Deola et al 11 have demonstrated that even after CD34 þ cell selection, MRD could still be detected in MM patient autografts. This possibly may be due to the fact that some CD34 þ stem cells circulating in MM patient blood could carry IgH VDJ gene rearrangements that will lead to MM relapse as shown by Szczepek et al 14 Previously, we have shown that AP carrying 1-10% tumor burden of primary patient specimens of various lymphomas purged with reovirus resulted in successful elimination of malignant cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Although a multicenter randomized trial has shown that MM minimal residual disease (MRD) depletion by CD34-positive cell selection does not improve overall or PFS, 7 recent clinical evidence supports significant differences in PFS of patients with 'low' graft contamination (o4.5 Â 10 5 plasma cells/kg) versus 'high' graft contamination (X4.5 Â 10 5 plasma cells/kg). 8 In addition, syngeneic twin transplantation has shown significantly lower relapse risk than autotransplantation for MM, again suggesting that graft contamination may impact outcome following ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…52 CD34 þ cell selection of the graft became quite popular more than a decade ago. However, two randomized studies evaluating the importance of CD34 þ cell selection in myeloma patients showed that the outcome was not affected by graft selection despite a 2-3 log decrease in the amount of tumour cells 53,54 and currently CD34 þ cell selection is rarely performed in the autologous setting, with the possible exclusion of some clinical study protocols for treatment of severe autoimmune diseases. 55 CD34 þ cell selection of the graft affects not only the potential tumour cell contamination, but also importantly the amount of accessory and immune cells given to the patient to support HDT.…”
Section: Tumour Cell Contamination Of the Graftmentioning
confidence: 99%